PENGARUH ONLINE CUSTOMER RIVIEW, E-SERVICE QUALITY, LIVE STREAMING TERHADAP MINAT BELI PRODUK FASHION DI E-COMMERCE SHOPEE - Fauzan Fananny; Muji Rahayu, Tri Septin; Muhammad Agung Miftahuddin; Luthfi Zamakhsyari (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of online customer reviews, e-service quality, live streaming on purchase intention in fashion products on e-commerce shopee. This study uses a quantitative approach. The population in this study is generation Z in Purwokerto City. The sample used was 126 respondents. The sampling technique in this study used purposive sampling technique. Data analysis was carried out using SmartPLS 3.0 to determine the relationship between variables. The results of this study indicate that the e-service quality and live streaming variables have a positive and significant effect on purchase intention. While the online customer review variable does not affect purchase intention.